(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
In addition to the intestinal manifestations, the inflammatory bowel disease of Crohn’s disease (CD) is also associated with some extra-intestinal symptoms, such as ulcers in the oral cavity, which tend to aggravate the general care and compromise the patient’s general well-being. The following case presents a 23-year-old patient with a CD complicated by severe oral symptoms persisting despite early treatments, including recalcitrant recurrent aphthous stomatitis, mucosal swelling, and gingivitis. The patient was treated using a multidisciplinary approach that integrated both gastroenterology and dental aspects. Systemic corticosteroids, immunosuppressive therapy, topical corticosteroids, antibacterial mouth rinses, dietary advice, and general support were among the treatment modalities provided. This comprehensive plan, which significantly enhanced the patient’s quality of life, also demonstrated improvement in oral health and a decrease in signs and symptoms. This case demonstrates how interdisciplinary strategies can help in CD oral manifestations management, given the enhancement of the patient’s health. Further investigation and case studies are needed to refine treatment strategies and expand understanding of these oral lesions and concerns regarding them.